Assessment of different stabilizer materials in cold in-place recycling method - Nor Aklima Khidir, author; Haryati Yaacob, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017